Aspectos somáticos da conquista do Eu em D. W. Winnicott - Laurentiis, Vera Regina Ferraz de (2008)
The objective of this paper is to explain the somatic aspects inherent to the Winnicottian maturational theory from the initial moment to the so-called I am phase, to assist the psychoanalyst with the comprehension of the clinical phenomena that occur in the soma but are not able to be verbalised. To this end, I have briefly expounded on the theoretical change made by Winnicott and the substitution of the traditional psychoanalytical guidetheory of sexuality by the maturational theory and the Oedipal example for that of the baby on its mother s lap. The distancing from metapsychology and the consolidation of a descriptive language aims to draw closer to the clinical phenomena. Focusing on the interaction between the so-called living body and the human environment, highlighting the imaginative elaboration of the soma and the primary psychosomatic character of Winnicottian theory. Expounding on that which the author denominates as inhabiting the psyche in the soma and the integration of instinct with the self, which is at the foundation of future instinctive dualistic and/or pluralistic relations. Through these propositions, one can understand the author s sense of the I am phase, as that of a moment in which, with the constitution of a body scheme, the baby acquires a place to exist and experience the world